Magic Tree House Fact Tracker #16 Polar Bears and the Arctic a Nonfiction Companion to Magic Tree House #12 Polar Bears Past Bedtime - Osborne, Mary Pope; Boyce, Natalie Pope Murdocca, Sal (Random House New York, 2011)
Magic Tree House Research Guides are now Magic Tree House Fact Trackers! Track the facts with Jack and Annie! When Jack and Annie got back from their adventure inMagic Tree House #16: Polar Bears Past Bedtime, they had lots of questions. Why is the Arctic so cold? What did the first people of the Arctic eat? How do polar bears cross thin ice? What other animals live in the Arctic? Find out the answers to these questions and more as Jack and Annie track the facts. Filled with up-to-date information, photos, illustrations, and fun tidbits from Jack and Annie, the Magic Tree House Fact Trackers are the perfect way for kids to find out more about the topics they discovered in their favorite Magic Tree House adventures